Persepsi Siswa Tentang Pernikahan Dini Pada Remaja Di Pegatan Hulu - Nissa, Choirun; Erawati, Desi; Pamungkas, Ari (JURNAL KONSELING GUSJIGANG, 2023)
The number of teenagers of school age who are still doing early marriage, especially in Pegatan Hulu has an impact on births. The purpose of this study was to determine how school students' perceptions of early marriage and the factors causing early marriage. This type of research is qualitative with a descriptive approach that describes an event that is currently happening. Furthermore, identifying informants using purposive sampling techniques based on the criteria for the average age of 15-18 years, totaling 10 students from two schools. The location of this research is at SMAN 1 Katingan Hulu and Madrasah Aliyah Al-Ma'arif in Pegatan Hulu, Katingan Kuala District. Data were collected by interview and observation which were analyzed using data reduction, data presentation, and verification or data withdrawal. From the findings, it was obtained that students' perceptions of early marriage were marriages under the age of 19 years by teenage boys and girls. With various factors, one of which is economic factors, pregnancy out of wedlock, dropping out of school, and promiscuity.